Assessment of the organotin pollution in the coastal sediments of the Western Arabian Gulf, Saudi Arabia. (February 2019) - Hassan, Akere Taiwo; Qurban, Mohammed; Manikandan, Karuppasamy; Tawabini, Bassam; Basheer, Chanbasha; Periyadan, Krishnakumar
Abstract: Organotin compounds (OTCs) are persistent pollutants and are considered as chemicals of environmental concern. They enter the marine environment from the antifouling paints containing organotin compounds on the hulls of ships and boats. We report the results of a study conducted in 2015 on the level of butyltins (TBT, DBT, and MBT) and phenyltins (TPhT, DPhT, and MPhT) in the sediments collected from three fishing harbors (Jubail, Khobar, and Qatif) and a reference site (Half Moon Bay). The concentrations of OTCs in the sediments vary widely among the different sampling locations. Overall, the phenyltins contribute more than the butyltins and the order of the abundance is: MPhT > DPhT > MBT > DBT > TPhT. In most stations, the concentrations of MBT are higher than DBT. The sediments from Khobar and Qatif are moderately polluted, whereas those from the Jubail are ranked as highly polluted. The concentrations of TBT at all study sites are less than the detection limit, and hence, the environmental and ecotoxicological risks are low. Highlights: Organotin compounds (OTCs) are chemicals of environmental concern and are persistent. Study analyzed Organotin compound (OTCs) concentrations in sediments from four coastal locations of Saudi Arabia. Concentrations of TBT in all of the study sites were less than the detection limits. Contribution of phenyltins were more than butyltins and the order of abundance was: MPhT > DPhT > MBT > DBT > TPhT. Sediments from the Jubail were highly contaminated when compared to the samples collected from Khobar and Qatif.